2012
DOI: 10.1002/jgm.2606
|View full text |Cite
|
Sign up to set email alerts
|

Lentiviral vector followed by protein immunisation breaks tolerance against the self‐antigen Her1 and results in lung cancer immunotherapy

Abstract: The ability of this vaccine protocol to break both T cell and B cell tolerance to a self-antigen likely explains its effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Heterologous prime-boost regimens that use two different vaccines to first prime the immune system and then boost its response have been shown to improve the efficacy of cancer vaccines in numerous preclinical animal models, and lentiviral vectors as the priming component have emerged as a promising new vaccine modality. [15][16][17][18][19] The priming component of CMB305 is LV305, which is a replication-incompetent, integration-deficient, improved third-generation lentiviral vector that contains RNA encoding for the full-length NY-ESO-1 protein. 20 Further, LV305 is based on the ZVex® platform, which has been shown to transduce dendritic cells through pseudotyping with an engineered Sindbis virus glycoprotein called SINVar1 that binds the C-type lectin receptor DC-SIGN (dendritic cell-specific intercellular adhesion molecule-3-grabbing non-integrin) expressed on immature dendritic cells.…”
Section: Introductionmentioning
confidence: 99%
“…Heterologous prime-boost regimens that use two different vaccines to first prime the immune system and then boost its response have been shown to improve the efficacy of cancer vaccines in numerous preclinical animal models, and lentiviral vectors as the priming component have emerged as a promising new vaccine modality. [15][16][17][18][19] The priming component of CMB305 is LV305, which is a replication-incompetent, integration-deficient, improved third-generation lentiviral vector that contains RNA encoding for the full-length NY-ESO-1 protein. 20 Further, LV305 is based on the ZVex® platform, which has been shown to transduce dendritic cells through pseudotyping with an engineered Sindbis virus glycoprotein called SINVar1 that binds the C-type lectin receptor DC-SIGN (dendritic cell-specific intercellular adhesion molecule-3-grabbing non-integrin) expressed on immature dendritic cells.…”
Section: Introductionmentioning
confidence: 99%
“…This was dramatically demonstrated by the improved protection of nonhuman primates from simian immunodeficiency virus when a vaccinia-based vaccine was followed by a gp160 protein-based vaccine [38]. This concept has been illustrated in a variety of infectious models as well as a various murine tumor models where viral vectors, including LVs, were used to prime the immune system followed by protein boost [3943]. While the reasons for the efficacy of heterologous prime-boost are still a matter of debate and are at least in part linked to inducing immune response against the vector in addition to the antigen, the order of the different vaccines used also appears to be important.…”
Section: Introductionmentioning
confidence: 99%
“…In a different experimental setting, mice immunized with the extracellular domain of the mEGFR developed a strong antibody response with high EGFR-antagonistic activity, which resulted in reduction of lung metastases (Ramírez et al, 2006, 2008). This anti-metastatic effect of the mEGFR vaccine also was abolished by in vivo depletion of the CD8+ T lymphocyte subpopulation (aguiar alpizar et al, 2012). Furthermore, it was demonstrated that an anti-EGFR antibody, but not a STKI, promotes an immunogenic cell death in a Lewis lung carcinoma model, involving induction of a CTL response in vivo (Garrido et al, 2011a).…”
Section: Egfr Oncogene Addiction May Reflect the Interconnection Of Smentioning
confidence: 99%